Relationship of Input and Output Variables with DEA (Data Envelopment Analysis) Approach: Efficiency Implementation Study in Library Science Journal SINTA 2 and 3 - Ibrahim, Cecep (Publication Library and Information Science, 2023)
When the impact produced by the output variable (H-Index) is greater than that of the input variable (Impact Factor), the quality of a journal is said to be efficient. This investigation aims to evaluate the effectiveness of SINTA 2 and 3-indexed library science journals. This study examines the relationship between input and output variables using the Data Envelopment Analysis (DEA) method to measure efficiency in a library science journal that is indexed by SINTA accredited 2 and 3. A data-driven technique for calculating the full factor efficiency of homogeneous decision units is called data envelopment analysis (DEA). If the impact produced by the ranking of the output variable (H-Index) is greater than that of the input variable (Impact Factor), then the Library Science Journal is said to be efficient. Four out of the eight library science journals indexed by SINTA 2 and 3 are deemed efficient, according to the study's findings. Jurnal Berkala Ilmu Perpustakaan dan Informasi, Jurnal Baca Dokumentasi dan Informasi, Jurnal Kajian Informasi dan Perpustakaan, dan Jurnal Pustakaloka: Jurnal Kajian Informasi dan Perpustakaan.